Revival of the fittest: exploding core-collapse supernovae from 12 to 25 M⊙. Issue 3 (28th March 2018) - Vartanyan, David; Burrows, Adam; Radice, David; Skinner, M Aaron; Dolence, Joshua
Abstract: We present results of 2D axisymmetric core-collapse supernova simulations, employing the Fornax code, of nine progenitor models spanning 12 to 25 M⊙ . Four of the models explode with inelastic scattering off electrons and neutrons as well as the many-body correction to neutrino-nucleon scattering opacities. We show that these four models feature sharp Si–O interfaces in their density profiles, and that the corresponding dip in density reduces the accretion rate around the stalled shock and prompts explosion. The non-exploding models lack such a steep feature, highlighting the Si–O interface as one key to explosion. Furthermore, we show that all of the non-exploding models can be nudged to explosion with modest changes to macrophysical inputs, including moderate rotation and perturbations to infall velocities, as well as to microphysical inputs, including reasonable changes to neutrino-nucleon interaction rates, suggesting that all the models are perhaps close to criticality. Exploding models have energies of a few × 10 50 erg at the end of our simulation, and are rising, emphasizing the need to continue these simulations over larger grids and for longer times to reproduce the energies seen in nature. Morphology of the explosion contributes to the explosion energy, with more isotropic ejecta producing larger explosion energies. We do not find evidence for the Lepton-number Emission Self-sustained Asymmetry. Finally, we look at proto-neutron star (PNS) properties and explore the role of dimension in our simulations. We find that convection in the PNS produces larger PNS radii as well as greater 'νμ ' luminosities in 2D compared to 1D.